2017
DOI: 10.1186/s12865-017-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide mediates immuno-pathological alterations in young chicken liver through TLR4 signaling

Abstract: BackgroundLipopolysaccharide (LPS) induces acute liver injury and the complex mechanisms include the activation of toll like receptor 4 (TLR4) signaling pathway in many species. However, immuno-pathological changes during TLR4 signaling under LPS stress in acute liver injury is poorly understood in avian species. The present investigation was therefore carried out to evaluate these alterations in TLR4 signaling pathway during acute liver injury in young chickens.ResultsAfter intraperitoneal injection of LPS or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
3
25
1
Order By: Relevance
“…As proinflammatory factors, IL-1, IL-6, and TNF-α have been used for evaluating inflammatory and infectious reaction and related immunity in humans and various animals including chickens ( Yang et al., 2014 ; Koronowicz et al., 2016 ; Huang et al., 2017 ). Tumor necrosis factor-alpha plays an important role in the pathogenesis of mammals' NAFLD ( Wigg et al., 2001 ) and has a close relationship with the liver damage including steatosis, fibrosis, and apoptosis ( Tomita et al., 2006 ; Zhang et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…As proinflammatory factors, IL-1, IL-6, and TNF-α have been used for evaluating inflammatory and infectious reaction and related immunity in humans and various animals including chickens ( Yang et al., 2014 ; Koronowicz et al., 2016 ; Huang et al., 2017 ). Tumor necrosis factor-alpha plays an important role in the pathogenesis of mammals' NAFLD ( Wigg et al., 2001 ) and has a close relationship with the liver damage including steatosis, fibrosis, and apoptosis ( Tomita et al., 2006 ; Zhang et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that EtOH feeding elevates plasma LPS and that L. plantarum prevents this effect of EtOH by an EGFR-dependent mechanism. LPS exposure has been shown to increase the expression of its receptor, TLR4, in different tissues, including the liver (19,20). Therefore, we evaluated TLR4 mRNA levels in liver.…”
Section: Plantarum Attenuates Alcohol-induced Liver Damage By Egfrmentioning
confidence: 99%
“…Although the prevention of liver damage by L. plantarum in the gut lumen provides strong support for the role of gut permeability and endotoxin flux in alcoholic liver damage, a direct effect of EtOH on liver cannot be ruled out. To gather further support on LPS-mediated liver damage, we evaluated the effect of EtOH and L. plantarum on the levels of plasma LPS and liver mRNA for TLR4 and MYD88, both known to be up-regulated by LPS exposure (19,20). L. plantarum in the diet attenuated EtOH-induced elevation of plasma LPS in WT and rtTA mice, which was blocked by doxycycline-mediated expression of dominant negative EGFR in rtTA-EGFR*-Tg mice.…”
mentioning
confidence: 99%
“…As pro-inflammatory factors, IL-1, IL-6, and TNF-α have been used for evaluating infectious and inflammatory reaction-associated immunity in humans and various animals including chickens [52][53][54]. TNF-α plays an important role in the pathogenesis of mammals' NAFLD [55] and has a close relationship with the liver steatosis, fibrosis, and apoptosis [56,57].…”
Section: Discussionmentioning
confidence: 99%